2011
DOI: 10.1002/imhj.20289
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a mental health consultation model and its impact on early childhood teachers' efficacy and competence

Abstract: Early childhood mental health (MH) consultants work closely with childcare teachers onsite to serve as a resource for childcare providers as they foster and enhance children's early development. The increase in the quality of care that can be supported through an early childhood MH consultation program makes this type of consultation an optimal tool for enhancing the childcare environment and overall child development. This article details the initial launch of the MH consultation program to childcare centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…Prior research on the current ECMHC model (Heller et al, 2011) has demonstrated that the majority of teachers rate their relationship with their ECMHC as highly positive; the average score was 5.5 out of 6, supporting pathway A in Figure 1. Because of the limited FIGURE 1 (A) Early childhood mental health consultation (ECMHC) logic model for intervention.…”
Section: Mhc-teacher Relationshipsupporting
confidence: 50%
See 4 more Smart Citations
“…Prior research on the current ECMHC model (Heller et al, 2011) has demonstrated that the majority of teachers rate their relationship with their ECMHC as highly positive; the average score was 5.5 out of 6, supporting pathway A in Figure 1. Because of the limited FIGURE 1 (A) Early childhood mental health consultation (ECMHC) logic model for intervention.…”
Section: Mhc-teacher Relationshipsupporting
confidence: 50%
“…The Tulane University Institute of Infant and Early Childhood Mental Health's ECMHC model has demonstrated that trained consultants can successfully implement a single standardized ECMHC model statewide (Heller et al, 2011). The program met the expectations for all four benchmarks observed: length of consultation (6 months), number of visits (10-12 visits), didactic sessions (five sessions), and developing positive relationships with teachers.…”
Section: Current Researchmentioning
confidence: 89%
See 3 more Smart Citations